Exploring The Impact of Traditional Childcare Practices on Child Development in Rural Andhra Pradesh - Suvarchala, M.; Kilaru, Yamuna (International Journal of Psychosocial Rehabilitation, 2025)
Andhra Pradesh, a state in southern India, is home to a diverse range of cultural traditions and practices, many of which have been passed down through generations. In rural communities across the state, traditional childcare practices continue to play a significant role in shaping the development of young children. This study employed a mixed methods approach to explore the impact of these traditional childcare practices on child development in rural Andhra Pradesh. The research was conducted in three villages, selected based on their demographic characteristics and the prevalence of traditional childcare practices. Data was collected through in-depth interviews, focus group discussions, and a survey. The findings suggest that traditional childcare practices have a multifaceted impact on child development. While some practices, such as the involvement of extended family members and the incorporation of cultural and religious rituals, were associated with enhanced social-emotional development and a stronger sense of cultural identity, other practices, like the use of harmful traditional remedies, had adverse effects on children’s physical health and cognitive abilities. The study highlights the complex and nuanced relationship between traditional childcare practices and child development in rural Andhra Pradesh. To promote holistic child development in these communities, it is essential to develop culturally sensitive interventions that build upon the strengths of traditional practices while addressing their potential drawbacks. By understanding the impact of traditional childcare practices, policymakers and practitioners can work towards creating a more inclusive and supportive environment for children in rural Andhra Pradesh.